Pengaruh Konflik Orang Tua terhadap Tingkat Kecemasan pada Remaja - Atika Fathur Rahmi (Universitas Palangka Raya, 2026)
Parental conflict is a significant risk factor that threatens the psychological well-being of adolescents. This study aims to review the relationship between parental conflict and anxiety levels in adolescents through a qualitative literature approach. Various research findings consistently show that high-frequency and high-intensity parental conflict contributes to increased anxiety, emotional insecurity, and maladaptive coping in adolescents. The mechanisms underlying this relationship include the emotional security theory, the cognitive-contextual framework, and the spillover hypothesis, each of which explains how conflict in the family system propagates psychologically to children. The results of this literature study confirm that adolescents who are regularly exposed to parental conflict show a significantly higher risk of developing generalized anxiety, social anxiety, and related internalizing problems. The family environment, particularly the quality of the parental relationship, is the dominant proximal determinant of adolescent mental health. Furthermore, parental conflict has been shown to undermine parent-child attachment, destabilize family functioning, and trigger chronic stress responses in adolescents who are still developing emotional regulation capacities. In the Indonesian context, this problem is particularly urgent given the high prevalence of mental health disorders among adolescents aged 15–24 years. Therefore, integrated preventive interventions involving families, schools, and mental health professionals are urgently needed.